Early imaging to detect bone metastatic disease of a 54-year-old woman with history of breast cancer: a case report - Dana, I. Made Bayu Surya; Atmaja, I. Nyoman Teri (International Journal of Advances in Medicine, 2023)
The World Health Organization (WHO) has predicted a global amount of 19 million cancer case in 2025. After the lungs and liver, bone is the third most common site of tumour spread. The bone is a dynamic tissue that plays a critical role not only in structural support and movement, a reservoir for minerals and energy, but also houses of the bone marrow, which is the main site of postnatal hematopoiesis. A 54-year-old Indonesian woman presented to orthopaedist with complaints of sudden left hip pain and progressive difficulty in walking for three weeks. She reported severe pain that is exacerbated by any physical activity and movement. She has a medical history of breast cancer (pathologically confirmed in Sanglah General Hospital) which had undergone radiotherapy and chemotherapy a year ago. Outpatient left hip X-rays revealed lytic lesions at left acetabulum to left ilium, suggestive of metastatic disease. The established imaging techniques projectional radiography, skeletal scintigraphy, computed tomography (CT), magnetic resonance imaging (MRI), and positron emission tomography (PET) have undergone further development, with a resulting improvement in their diagnostic yield.